2011
DOI: 10.3892/etm.2011.244
|View full text |Cite
|
Sign up to set email alerts
|

Trifluorothymidine exhibits potent antitumor activity via the induction of DNA double-strand breaks

Abstract: Abstract. taS-102 is an oral anticancer drug composed of trifluorothymidine (TFT) and TPI (an inhibitor of thymidine phosphorylase that strongly inhibits the biodegradation of TFT). Similar to 5-fluorouracil (5FU) and 5-fluoro-2'-deoxyuridine (FdUrd), TFT also inhibits thymidylate synthase (TS), a rate-limiting enzyme of DNA biosynthesis, and is incorporated into DNA. TFT exhibits an anticancer effect on colorectal cancer cells that have acquired 5FU and/or FdUrd resistance as a result of the overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…13) or cotreatment with FTD and TPI (i.e., TAS-102; refs. 13, 34) could result in DNA fragmentation detectable by alkaline gel electrophoresis, in situ nick translation (13), or pulse field gel electrophoresis under the neutral condition (34).…”
Section: Discussionmentioning
confidence: 99%
“…13) or cotreatment with FTD and TPI (i.e., TAS-102; refs. 13, 34) could result in DNA fragmentation detectable by alkaline gel electrophoresis, in situ nick translation (13), or pulse field gel electrophoresis under the neutral condition (34).…”
Section: Discussionmentioning
confidence: 99%
“…5-Trifluorothymidine, commercially known as trifluridine, is an antiviral agent employed in ophthalmic solutions for the treatment of herpes virus simple (HVS) [22]. This compound can also induce double-strand DNA breaks and inhibit the thymidylate synthase when it is transformed to its phosphorylated form, displaying antitumoral activity [23]. The combination of this compound with an inhibitor of the thymidine phosphorylase, to inhibit degradation of trifluridine, is currently undergoing a Phase III clinical trial with patients with refractory metastatic colorectal cancer (NCT01607957) [24].…”
Section: Introductionmentioning
confidence: 99%
“…There are also now conflicting data regarding TFT-induced DNA fragmentation. While Suzuki et al demonstrated that TFT incorporation into DNA resulted in single-and double-strand breaks and subsequent activation of DNA repair cascades, DNA fragmentation was not observed with a more recent study by Matsuoka et al [30,32]. Both studies, however, demonstrated that TAS-102 treatment resulted in massive TFT incorporation into DNA and in activation of similar DNA damage response pathways, which involve phosphorylation of Chk1 and cycle arrest during the G2/M-phase.…”
Section: Inhibition Of Cell Cycle By Tas-102mentioning
confidence: 88%
“…Inhibition of TS does not correlate with the antitumor activity of FTD but there is a positive correlation between the antitumor activity of TAS-102 and the amount of TFT incorporated into human cancer xenograft DNA [26,28]. It has been shown previously that DNA incorporation of TFT results in increased DNA fragmentation due to single-and double-stranded DNA breaks [29,30]. However, the mechanisms underlying this process have not been fully elucidated.…”
Section: Inhibition Of Cell Cycle By Tas-102mentioning
confidence: 97%
See 1 more Smart Citation